Study on mechanical properties of steel fiber reinforced concrete interface transition zone based on unified phase-field theory - Huiming WANG; Guozheng WU (Journal of Hebei University of Science and Technology, 2023)
In order to investigate the impact of different modeling methods of interface transition zone on the mechanical properties, damage and failure process of steel fiber reinforced concrete in numerical simulation, based on the unified phase-field theory and the cohesive zone model, two methods were used to establish a numerical calculation model of the interface transition zone of steel fiber reinforced concrete for the tensile test of concrete specimens containing a single steel fiber to compare and analyze the effects of different modeling methods on the mechanical properties and failure modes of steel fiber reinforced concrete, and the effects of different factors on the ultimate tensile strength of concrete containing a single steel fiber were investigated. The results show that the phase-field theory model for the matrix part and the cohesive zone model for the interface transition zone have good accuracy and reliability in both the calculation results and mesoscopic failure morphology; the tensile strength of steel fiber reinforced concrete with the initial crack location of 30 mm and 35 mm is 308% and 757% higher than that of 25 mm, respectively; the tensile strength of steel fiber reinforced concrete with the steel fiber embedding angle of 15°, 30°, and 45° is 122%, 308%, and 489% lower than that of 0°, respectively; the reinforcement effect of steel fiber is greatly influenced by the initial crack location and the embedding angle of steel fiber, and is relatively less influenced by the diameter of steel fiber. Adopting the unified phase-field theory can lower the analysis difficulty while guarantee higher computational accuracy, which provides theoretical reference for the study of the damage and fracture process of steel fiber reinforced concrete.